Nivel de apropiación de la idea de discontinuidad de la materia en alumnos de Bachillerato. Implicaciones didácticas - Gentil González, C.; Iglesias Blanco, A.; Oliva Martínez, José Mª (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
In this paper we will try show how those pupils starting Secondary Education have scarcely assumed the discontinuous nature of matter and little progress about it is noticed at the end of their studies.